Subjectivity of discourse and translation: functional-cognitive approach. Issue 3 (1st September 2016) - Mammadov, Azad; Ziyadova, Lalandar
Abstract: The paper aims to explore some of the issues that arise in the study of subjectivity of discourse and its relation with translation from a new perspective, identified as the functional-cognitive approach. Despite the obvious role of language and culture in translative discourse, ultimately, individual practices based on subjectivity define its nature. In order to justify this methodology, we analyze translation of information structure of texts with pragmatically marked word order, as well as metaphors, metonymy and figurative language more generally (both universal and cultural). Creative language and therefore analysis of its use, is often key to understanding why subjectivity matters in translative discourse. The Introduction outlines key theoretical issues and concepts, giving a critical view to translative discourse. It also deals with the issue of intention in translative discourse. The main parts of the paper explore the functional-cognitive strategies of inversion and metaphorically used words respectively employed in the original text. This includes the ways the translator delivers them in the text and adds his/her own preferences to the original text paving the way to subjectivity in translative discourse. Thus, the translator as a receiver and a sender is the core element of our research.